In-depth analysis of the mode of action of resveratrol: genome-wide characterization of G-quadruplex binding properties - Ana Soriano-Lerma; Victoria Sánchez-Martín; Javier Murciano-Calles; Matilde Ortiz-González; María J. Tello-López; Virginia Pérez-Carrasco; Ángel Linde-Rodríguez; Inmaculada Ramírez-Macías; Irene Gómez-Pìnto; Inmaculada López-Aliaga; Miguel Soriano; Jose A. Garcia Salcedo (Cellular & Molecular Biology Letters)
Abstract Background Resveratrol (RSV) is one of the most studied and used biomolecules, for which many pharmacological effects targeting multiple tissues have been described. However, a common underlying mechanism driving its full pharmacological activity has not been described in detail. G-quadruplexes (G4s) are non-canonical nucleic acid structures found in regulatory genomic locations and involved in controlling gene transcription, telomere maintenance, or genome stability, among others. This study provides a genome-wide characterization of RSV G4-binding properties, explaining its multi-target traits. Methods Immunofluorescence assays using a nucleolar and a G4-specific antibody were used to characterize RSV cellular effects on the nucleolus and G4 stabilization. DNA damage and cell cycle analyses were performed via western blot and flow cytometry. Breaks lLbeling In Situ and Sequencing (BLISS) was used to map double strand breaks (DSB) in response to treatment, and identify G4s targeted by RSV. mRNA sequencing was used to identify changes at the transcriptional level upon treatment and relate them to a direct targeting of G4s. Biophysical assays (circular dichroism, ultraviolet–visible [UV–Vis] titration, differential scanning calorimetry, and nuclear magnetic resonance) were used to characterize RSV–G4 interactions. Lastly, luciferase-based transcription assays were performed to confirm RSV–G4 interaction in vitro and its direct influence on gene expression. Results In a cellular context, RSV treatment showed classic G4-ligand effects, such as nucleolar disassembly, inhibition of RNA polymerase I, DNA damage, and cell cycle arrest. RSV was shown to stabilize cellular G4s, which accumulated around double strand breaks in the promoters of differentially expressed genes. Upon treatment, G4 stabilization triggered DNA damage and controlled gene expression. The interaction between RSV and target G4s was confirmed in vitro by biophysical assays and through luciferase-based transcription assays. Conclusions A G4-dependent mode of action was demonstrated as the main mechanism underlying RSV pleiotropic effects, along with the identification of target genes and G4s. This in-depth analysis of the mode of action of RSV will be helpful to improve its therapeutic potential in a wide variety of health scenarios. Graphical Abstract